Visualizing the Human Reproductive System Material Through Web-based E-module - Rahmawati, Rina; Octavia, Bernadetta; Ayuningtyas, Dwi; Nugraha, Aditya Dirgantara (Journal of Education Technology, 2024)
The 21st century is the digital age, so learning is expected to take advantage of technology. Teachers have not utilized technology as much as possible so learning in the classroom is not optimal. This study aims to develop a web-based e-module teaching material on the human reproductive system for high school/MA class XI students. The research and development model uses ADDIE. The research subjects consisted of 1 media expert, one material expert, two biology teachers, and 30 students. Data collection methods consist of observation, interviews, and questionnaires. Data analysis used descriptive qualitative and quantitative descriptive. The results showed that the assessment score of media experts was 3.82 (Very Valid); the score of material experts was 3.50 (Valid); the score of the biology teacher was 3.91 (Very Valid), and a student score of 3.46 (Valid). Therefore, it can conclude that the web-based e-module on the human reproductive system material is suitable for biology learning. Web-based e-modules can help class XI students to study independently anytime and anywhere and to understand material on the human reproductive system.